Group representation for the working class? Opinion differences among occupational groups in Germany - Lea Elsässer; Armin Schäfer (Max Planck Institute for the Study of Societies, 2016)
In this paper, we take up the burgeoning debate about the underrepresentation of the working class in politics. In the literature section we discuss theories of group representation and look at recent empirical studies of responsiveness that have begun to disaggregate public opinion by sociodemographic categories. Empirically, we analyze a dataset of more than 700 survey items collected in Germany between 1980 and 2012. The analysis shows that respondents within one social class are more similar to each other than to members of other classes and that class-based differences outweigh those of education, region, or gender. While opinion differences are not always large, they can reach 50 percentage points. There are frequently gaps of between 20 or 30 percentage points in support for or opposition to policy changes. Since workers' opinions tend to differ from the opinions of those groups who are well represented in parliament, their numerical underrepresentation might bias decisions against them, as recent studies suggest. – – In diesem Discussion Paper greifen wir die aktuelle Debatte über die politische Unterrepräsentation der Arbeiterklasse auf. Im Literaturteil stellen wir Kernargumente der Theorien deskriptiver Repräsentation dar und verknüpfen diese mit aktuellen Studien aus der empirischen Responsivitätsforschung. Im empirischen Abschnitt analysieren wir einen von uns erstellten Datensatz mit mehr als 700 Sachfragen, die jeweils nach der Zustimmung oder Ablehnung einer vorgeschlagenen Politikänderung fragen. Die Sachfragen stammen aus Umfragen, die zwischen 1980 und 2012 erhoben wurden. Wir zeigen, dass sich die Befragten innerhalb einer sozialen Klasse in ihren Einstellungen systematisch ähnlicher sind als Befragte aus unterschiedlichen sozialen Klassen. Zudem sind Einstellungsunterschiede zwischen sozialen Klassen größer als zwischen anderen sozialen Gruppen (Bildung, Region, Geschlecht); sie betragen häufig mehr als 20 oder 30 Prozentpunkte. Da Arbeiter sich von den Gruppen unterscheiden, die zahlenmäßig stark im Parlament vertreten sind, könnte dies vermehrt zu Politikentscheidungen ent gegen ihren Interessen führen.
Keywords: 300